DIGITAL BASED NEWS PRODUCTION MANAGEMENT STRATEGY IN RESPONDING THE CHALLENGES OF MEDIA CONVERGENCE - Mandasari, Zeintika (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to analyze digital-based news production management strategies in addressing the challenges of convergence, with a focus on content planning, newsroom workflow management, digital technology utilization, and the application of journalistic ethics and professionalism. The research method employed a descriptive qualitative approach, with data collection techniques including in-depth interviews, participant observation, and documentation studies. The informants included editors-in-chief, editors, content producers, and journalists at several media outlets that have adopted a multiplatform newsroom model. Data analysis was conducted using thematic analysis techniques through stages of reduction, categorization, and conclusion drawing. The results indicate that digital-based news production management strategies include early multiplatform planning, newsroom integration to improve coordination, the use of content management systems (CMS) and analytics tools for production efficiency, and the implementation of strict ethical guidelines through verification and fact-checking mechanisms. The findings also revealed obstacles such as limited human resources, organizational cultural resistance, and ethical dilemmas stemming from the dominance of audience data.